(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Polyherbal feminine hygiene wash products have gained significant popularity in recent years due to their perceived benefits for women’s intimate health. The Indian fast-moving consumable goods (FMCG) market is flooded with various brands of feminine hygiene washes. Maintaining a balanced vaginal ecosystem necessitates the use of active substances in these washes. Products marketed as medically oriented cleansers to healthcare professionals are classified as cosmetics. The widespread use of feminine wash (soap) among women of reproductive age aims to alleviate symptoms linked to vaginal infections, such as itching, burning sensations, vaginal discharge, and unpleasant odors. Vaginal infections impact a significant proportion, ranging from 10 to 75%, of women during their reproductive years, potentially stemming from yeast, bacteria, or parasites. Understanding the effects of ingredients in feminine hygiene wash formulations is crucial in managing these concerns. This paper aims to explore the cognizance, formulation and health implications associated with polyherbal feminine hygiene washes. It provides an overview of the formulation, ingredients, and claims made by these products. Additionally, it addresses the scientific evidence and potential risks linked to their use. The paper seeks to inform consumers, healthcare professionals, and policymakers about the key aspects of polyherbal feminine hygiene washes and their implications for women’s health. In conclusion, this review provides a collective dataset regarding different chemical and polyherbal hygiene wash products available in the market, fostering a comprehensive understanding of these product’s landscape. The findings underscore the need for informed decision-making and regulatory considerations in the usage of these products to ensure women’s well-being.